Lövsuccessioner i sluttningar längs nedre Umeälven - Renström, Andreas (2006)
Secondary deciduous forests, which have their origin in earlier pasture- and meadow-land in slopes along the lower reaches of the Ume river, are thought to contain high nature conservation values, in spite of a relatively low age. The aim of this study was to clarify how factors as historical use, exposition, disturbance dynamics and successional age influences the conservation values in these types of riparian forests and how this can be implicated in the practical work with conservation and management at Umeå municipality. Sample plots were placed in seven stands with a variation of their historical use, exposition, disturbance dynamics and age of succession. Conservation values as structure, tree-regeneration, abundance and composition of vascular plants, amount of dead wood and the abundance of signal-species were measured and registered. The species composition and especially the composition of tree species, differed between forests with different exposition and different historical use. Abundance and regeneration of Norway spruce (Picea abies (L.) Karst.) were high in north sloping stands. The volume of dead wood was generally high in all stands, but the proportion of dead wood with large (> 25 cm) diameters and within late decay, increased with successional age. Older stands had more signal species but their abundance also seem to be related to historical land-use.